POPULATION DISTRIBUTION AND DENSITY CHANGING PATTERN IN SUMATERA UTARA - Nilasari Siagian (Universitas Negeri Medan, 2021)
The purpose of this study was to determine the distribution of population density descriptions and patterns of change in North Sumatra. This type of research is library research (Library Research). Data collection techniques are carried out by utilizing existing facilities in the library, such as books, magazines, documents, secondary data records, statistical data, or pure library research related to the object of research. The analytical method provides a clear, objective, systematic, analytical, and critical description and description of the distribution and population density description: characteristics and patterns of change in North Sumatra. The initial step is achieved by collecting the required data, classifying it, describing it, and then analyzing it. The results of this study explain that the distribution pattern and population density that occur are caused by spatial characteristics and geological changes. When viewed from the aspect of population density. The high population density in North Sumatra causes social problems such as congestion, poverty, health services, crime rates, settlements, unhealthy living environments, and others. The pattern of population distribution that occurs is geographical. The largest distribution is still throughout the East Coast region, wherein that region there are the largest number of districts (above 5% of the province's population).Keywords: Population, Distribution, Density, Spatial